Optimalisasi Ekonomi Kreatif Warisan Sunan Sendang: Pemberdayaan Pengrajin Batik Berbasis Transformasi Tepat Guna - Sifwatir Rif'ah; Moh. Nasrul Amin (GUYUB: Journal of Community Engagement, 2024)
Batik Sendang Lamongan is one of the potentials of Sendangagung village inherited from the legacy of Sunan Sendang that needs to be developed and preserved. The majority of its batik artisans are aged 50 and above. Meanwhile, the population in Sendangagung village is predominantly represented by millennials, totaling 1,281 individuals or 18.74 percent of the population. This means that Sendangagung is predominantly inhabited by the younger generation. The lack of involvement of the younger generation in batik making becomes a problem if not handled properly. On the other hand, Sendangagung village has many entrepreneurs and batik craftsmen. Considering the vast potential of the batik village, which is not matched by high interest or motivation from the younger generation, it deserves better attention from the village government and researchers to be continuously developed and preserved. This activity aims to optimize the creative economic potential of the younger generation. This dedication utilizes the Asset Based Community Development (ABCD) method, an asset-based approach owned by the Sendangagung village community. The results of this activity show that not only are the youth of the village enthusiastic about participating in the mentoring from start to finish, but also their batik skills are extraordinary. This is evidenced by the remarkable batik works they produced during the mentoring process. Furthermore, post-mentoring, the younger generation of the village feels a great responsibility to continue participating in preserving the village's culture.